Intercultural communication and racism in a tourist context. Participant observation of raciolinguistic practices - Rodríguez-Iglesias, Ígor (2023)
This article deals with intercultural communication on the basis of discursive practices observed in situ in a tourist context. The study focuses on interactional differences with respect to skin colour and the geographical and cultural origin assumed by the local interlocutor. The methodology used is qualitative, based mainly on participant observation with a decolonial analysis within the studies of critical ethnographic sociolinguistics and intercultural communication. The text problematises the categories that construct foreignness. Specifically, it uses the Fanonian framework that dichotomises between zones of Being and zones of non-Being, which differentiates between privileges and subalternity. The discursive microviolence is made explicit in the observed practices. The author argues that intercultural communication studies must observe the differential fact of the coloniality of being and power. The results of the study reveal how racism mediates discursive practices.